2019
DOI: 10.1017/s1355617719000420
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Heterogeneity on the Wisconsin Card Sorting Test in Schizophrenia Spectrum Disorders: A Cluster Analytical Investigation

Abstract: Objectives: The Wisconsin Card Sorting Test (WCST) is a complex measure of executive function that is frequently employed to investigate the schizophrenia spectrum. The successful completion of the task requires the interaction of multiple intact executive processes, including attention, inhibition, cognitive flexibility, and concept formation. Considerable cognitive heterogeneity exists among the schizophrenia spectrum population, with substantive evidence to support the existence of distinct cognitive phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 69 publications
(92 reference statements)
0
16
1
1
Order By: Relevance
“…We are unaware of other studies that have aimed to classify countries based on simple open-access variables, and that can stratify the countries based on the number of COVID-19 cases. Most of the previous research using unsupervised machine learning clustering algorithms on health research has focused on individuals and diseases [16][17][18][19] . This work complements the available evidence at the individual level with preliminary information on clusters at the country level, with potential relevant applications in the current COVID-19 pandemic.…”
Section: Results In Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…We are unaware of other studies that have aimed to classify countries based on simple open-access variables, and that can stratify the countries based on the number of COVID-19 cases. Most of the previous research using unsupervised machine learning clustering algorithms on health research has focused on individuals and diseases [16][17][18][19] . This work complements the available evidence at the individual level with preliminary information on clusters at the country level, with potential relevant applications in the current COVID-19 pandemic.…”
Section: Results In Contextmentioning
confidence: 99%
“…This approach is considered a paradigm in unsupervised machine learning, because it assigns the elements into clusters which were unknown at the beginning of the analysis 15 . A few authors have used this methodology in clinical and public health research [16][17][18][19] .…”
Section: K-meansmentioning
confidence: 99%
“…Waltz suggests that excessive cognitive rigidity is likely to be characteristic of subgroups of patients with specific disorder profiles (3,12). This idea is supported by empirical studies that have detected subgroups of patients with different performance on the WCST (14)(15)(16). For instance, patients with a general and marked executive functioning impairment showed lower IQ and severe negative symptomatology.…”
Section: Introductionmentioning
confidence: 93%
“…In consequence, these deficits might result in hypoactivation of the intraparietal cortex during the incongruence condition. It has repeatedly been shown that schizophrenia comprises a very heterogeneous group of symptoms or even level of cognitive performance [ 45 ]. These differences might potentially also affect the functional outcome quantitatively.…”
Section: Discussionmentioning
confidence: 99%